2019
DOI: 10.1038/s41467-019-13127-z
|View full text |Cite
|
Sign up to set email alerts
|

Multisite phosphorylation drives phenotypic variation in (p)ppGpp synthetase-dependent antibiotic tolerance

Abstract: Isogenic populations of cells exhibit phenotypic variability that has specific physiological consequences. Individual bacteria within a population can differ in antibiotic tolerance, but whether this variability can be regulated or is generally an unavoidable consequence of stochastic fluctuations is unclear. Here we report that a gene encoding a bacterial (p)ppGpp synthetase in Bacillus subtilis, sasA, exhibits high levels of extrinsic noise in expression. We find that sasA is regulated by multisite phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 65 publications
0
54
0
Order By: Relevance
“…S4D-F). More broadly, given PrkC phosphorylates hundreds of proteins involved in diverse essential processes (Libby, Goss, and Dworkin 2015;Libby, Reuveni, and Dworkin 2019;Pompeo et al 2015;Shah et al 2008), PrkC might act to simultaneously tune their overall activities in response to nutrient conditions. If so, decoupling one PrkC regulated process, such as cell wall synthesis, from the others should result in fitness defects, as this would cause one biosynthetic process to proceed too fast or slow relative to the others.…”
Section: Prkc Contains a Cytoplasmic Kinase Domain And A Periplasmic mentioning
confidence: 99%
See 1 more Smart Citation
“…S4D-F). More broadly, given PrkC phosphorylates hundreds of proteins involved in diverse essential processes (Libby, Goss, and Dworkin 2015;Libby, Reuveni, and Dworkin 2019;Pompeo et al 2015;Shah et al 2008), PrkC might act to simultaneously tune their overall activities in response to nutrient conditions. If so, decoupling one PrkC regulated process, such as cell wall synthesis, from the others should result in fitness defects, as this would cause one biosynthetic process to proceed too fast or slow relative to the others.…”
Section: Prkc Contains a Cytoplasmic Kinase Domain And A Periplasmic mentioning
confidence: 99%
“…While this initial study focused on cell wall synthesis, PrkC and its homologs in other bacteria Cuenot et al 2019;Wamp, Rutter, Rismondo, Jennings, Möller, et al 2020) phosphorylate hundreds of proteins involved widely divergent cellular processes (Pereira, Goss, and Dworkin 2011;, as well as controls cell growth via modulation of (p)ppGpp synthesis (Libby, Reuveni, and Dworkin 2019). This suggests that PrkC might function as a cellular rheostat, tuning the activities of many different cellular processes in response to lipid II so that their activities run at equivalent rates across the range of nutrient conditions.…”
Section: Prkc Contains a Cytoplasmic Kinase Domain And A Periplasmic mentioning
confidence: 99%
“…2) 41 . In addition, upregulation of the genes associated with staphylococcal "cell wall stimulon" 28,42,43 , such as spsA (4.3-fold), ssaA (5.9-fold), relP (5.8-fold) and sasA (4.3-fold) was also found. Thus, mechanism of reduced DAP/VCM susceptibility by mprF mutation may be resulted from changes in CW/CM metabolism.…”
mentioning
confidence: 96%
“…We found that treatment with cell wall antibiotics, either at lethal or sublethal concentration, promote persister formation by inducing accumulation of (p)ppGpp through the (p)ppGpp synthetase YwaC. ywaC is a component of the cell envelope stress regulon whose transcription is known to be induced by cell envelope damage (D’Elia et al, 2009; Eiamphungporn and Helmann, 2008; Libby et al, 2019), likely explaining its production of (p)ppGpp upon cell wall antibiotic stress. For the soil bacterium B. subtilis , the evolution of this regulation may be shaped by fitness advantage from its habitat to enhance survival to diffusible antimicrobials from neighboring microbes.…”
Section: Discussionmentioning
confidence: 92%